2017
DOI: 10.1088/1475-7516/2017/01/002
|View full text |Cite
|
Sign up to set email alerts
|

Extended vector-tensor theories

Abstract: Abstract. Recently, several extensions of massive vector theory in curved space-time have been proposed in many literatures. In this paper, we consider the most general vector-tensor theories that contain up to two derivatives with respect to metric and vector field. By imposing a degeneracy condition of the Lagrangian in the context of ADM decomposition of space-time to eliminate an unwanted mode, we construct a new class of massive vector theories where five degrees of freedom can propagate, corresponding to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
132
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 55 publications
0
132
0
Order By: Relevance
“…Field redefinitions of this kind have been studied in tensorial notation in [49]. They have also been used to screen the cosmological vector field [50] and to study Weyl geometry as a vector-tensor theory [51,52].…”
Section: B Mixing With Spin-1 Fieldsmentioning
confidence: 99%
“…Field redefinitions of this kind have been studied in tensorial notation in [49]. They have also been used to screen the cosmological vector field [50] and to study Weyl geometry as a vector-tensor theory [51,52].…”
Section: B Mixing With Spin-1 Fieldsmentioning
confidence: 99%
“…Their cosmological perturbations, in the framework of the effective theory of dark energy (see e.g., [18]), are studied in [19]. Analogously, similar constructions for vector interactions were introduced in [20] and a classification for degenerate vector-tensor theories up to quadratic order was given in [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, [6], the authors have shown that the galileon-like terms cannot be introduced in a flat spacetime under the assumption of U (1) invariance, although in a curved space-time the vector Horndeski term can be allowed [7]. Once we abandon the U (1) gauge invariance, one can investigate a broad class of theories of massive vector field [8][9][10][11][12][13]. Theoretical developments in the theories of massless/massive vector fields may have interesting impacts for cosmology, such as cosmic inflation [14], the generation of primordial magnetic fields on large scales (see [15] for a review), or dark energy (see also e.g.…”
Section: Introductionmentioning
confidence: 99%